The Relationships Among Curriculum Management, Teacher Professional Development, Educational Technology Integration, and Teaching Effectiveness - Sofia Nur; Azhariah Rachman; Gamar Al Haddar; Petrus Jacob Pattiasina (PT. BATARI EDU CALYA, 2026)
This study examined the relationships among curriculum management, teacher professional development, educational technology integration, and teaching effectiveness in contemporary educational settings. A quantitative cross-sectional survey design was employed with 200 primary and secondary school teachers. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using descriptive statistics, reliability and validity testing, correlation analysis, and multiple regression analysis. The findings indicate that curriculum management, teacher professional development, and educational technology integration each have a positive and significant effect on teaching effectiveness. Teacher professional development emerged as the most influential factor, followed by educational technology integration and curriculum management. Collectively, the three independent variables explained a substantial proportion of the variance in teaching effectiveness, underscoring the importance of an integrated approach. The findings demonstrate that effective curriculum planning, continuous teacher development, and meaningful technology use are essential to strengthening instructional quality. They also provide important implications for educators, school leaders, and policymakers seeking to improve teaching effectiveness and educational outcomes in the context of twenty-first-century learning.